Practical PC - Parsons, June Jamrich; Oja, Dan (Practical series, 2014)
Part of the Practical series, this text offers an engaging, interactive approach to teaching PC concepts. It provides information on concepts, skills, and tips to become a proficient computer user in a friendly, accessible approach